Towards teachers' empowerment through teacher professional development programs provided by an NGO development project: An exploratory study - Aboelkhair, Sara Kamel (AUC Knowledge Fountain, 2018)
This qualitative study explores the empowering practices in teacher professional development programs held by an NGO development project for community school teachers. The literature review is divided into two main sections. The first section provided insights of the conceptual frameworks of professional development and empowerment along with international best practices. The second section focuses on the concept of community based learning, and the historical background on community schools in Egypt. Data was collected using semi-structured interviews, document analysis, and observations. The participant were 35 composed of facilitators/teachers, project manager, students, and mentors. The findings showed that while teachers where empowered in some dimensions, they are other aspects in which they were not fully empowered in yet. The paper concludes with practical implications, future recommendations, and limitations.